USE JD-R THEORY TO EXPLORE THE RELATIONSHIP BETWEEN EMPLOYEE EXPERIENCE AND EMPLOYEE ENGAGEMENT—TAKING JOB DEMANDS AS THE MODERATING VARIABLE - Yin, Mei Jhen; Chen, Chi Yu; Yang, Yi Wen; Hsu, Po Han (PEOPLE: International Journal of Social Sciences, 2024)
Past research has proven that employee experience has a positive impact on employee engagement. Based on the conceptual framework of Job Demands-Resources model (JD-R) model, this study regards efficient employee experience as a job resource to explore the impact of "employee experience" and” job demands” on employee engagement in organizations. Work requirements are further divided into challenge demand and hindrance demand. This study adopts the experimental design of the scenario method and uses two two-factor independent sample designs, namely 2x2(employee experience is high / employee experience is low x challenging job demands is high / challenging job demands is low) and 2x2(employee experience is high / employee experience is low x hindering job demands is high / hindering job demands is low).A total of 176 valid questionnaires were collected. The research results found that when employee experience is high, employee engagement is higher than when employee experience is low. Employee experience and job demands have an interactive effect on employee engagement. When employee experience is high, employee engagement will be higher when challenging job demands are added than when hindering job demands are added. It is expected that the results of this study can help in theoretical and practical applications